The book - Borsuk, Amaranth, 1980- (Cambridge, MA : The MIT Press, 2018)
"The Book tracks the ways the book's physical form and artistic content have historically inspired one another's evolution. Borsuk shows that in order to see where books might be going, we must think of them as objects whose physical shape has experienced a long history of experimentation and play. Rather than bemoaning the death of books or creating a dichotomy between print and digital media, Borsuk points to their continuities, positioning the book as a changing technology and highlighting the way poets and artists in the 20th and 21st centuries have pushed us to rethink our definitions of the term. Instead of a teleological story of ever-improving legibility, distribution, and engagement, the book's mutations tell us about our highly contingent cultural ideals of authorship and art. In mapping these shifts, Borsuk offers a path forward for those interested in shaping the book's future. More than a broad look at the book in the roles it plays, though (summed up by the chapter titles: book as object, book as content, book as idea, book as interface), this essential knowledge volume also offers a fascinating array of details, vignettes, and anecdotes: how the taste of insects for glue led to the use of stab binding, for example, or how humanism and Nazism could impact the typography used in mass market paperbacks in the UK, or how feeling "out of sorts" has its roots in printer's lingo"--
The book as object -- The book as content -- The book as idea -- The book as interface.
Includes bibliographical references (pages 297-307) and index.
Keywords: Books -- History; Libros -- Historia; Historia del libro; Printing -- History; Imprenta -- Historia